2013
DOI: 10.1136/bcr-2013-201616
|View full text |Cite
|
Sign up to set email alerts
|

Dural sinus filling defect: intrasigmoid encephalocele

Abstract: Filling defects of dural venous sinuses are considered to be a challenging problem especially in case of symptomatic patients. Many lesions have to be ruled out such as sinus thrombosis, arachnoid granulations and tumours. Encephalocele into dural sinus is also a rare cause of these filling defects of dural sinuses. Here, we report an extremely rare case with spontaneous occult invagination of temporal brain tissue into the left sigmoid sinus and accompanying cerebellar ectopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 21 publications
0
17
1
Order By: Relevance
“…Prior to the large systematic study published by Battal et al in 2015, there were only a small number of case series and case reports in the English literature . Battal et al reviewed a total of 6,160 brain MRIs, identifying a total of 21 herniations into the calvarium or dural venous sinuses in 20 patients, establishing a prevalence of 0.32%.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior to the large systematic study published by Battal et al in 2015, there were only a small number of case series and case reports in the English literature . Battal et al reviewed a total of 6,160 brain MRIs, identifying a total of 21 herniations into the calvarium or dural venous sinuses in 20 patients, establishing a prevalence of 0.32%.…”
Section: Discussionmentioning
confidence: 99%
“…Arachnoid granulations (AGs) are invaginations of the arachnoid membrane that protrude through gaps in the dura into the dural venous sinuses and occasionally the calvarium. They are functionally and histologically related to arachnoid villi, differing only in size and complexity, providing a route for cerebral spinal fluid (CSF) resorption into the bloodstream . Frequently seen on imaging, AGs are considered normal anatomic structures, though rare cases have been reported that indirectly implicate AGs with symptoms such as headache, tinnitus, CSF otorrhea, and intracranial venous hypertension …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations